OXA-48-like carbapenemases: the phantom menace - Poirel, Laurent; Potron, Anaïs; Nordmann, Patrice (Journal of antimicrobial chemotherapy, 2012)
OXA-48-type carbapenem-hydrolysing class D β-lactamases are increasingly reported in enterobacterial species. To date, six OXA-48-like variants have been identified, with OXA-48 being the most widespread. They differ by a few amino acid substitutions or deletions (one to five amino acids). The enzymes hydrolyse penicillins at a high level and carbapenems at a low level, sparing broad-spectrum cephalosporins, and are not susceptible to β-lactamase inhibitors. When combining permeability defects, OXA-48-like producers may exhibit a high level of resistance to carbapenems. OXA-163 is an exception, hydrolysing broad-spectrum cephalosporins but carbapenems at a very low level, and being susceptible to β-lactamase inhibitors. The bla(OXA-48)-type genes are always plasmid-borne and have been identified in association with insertion sequences involved in their acquisition and expression. The current spread of the bla(OXA-48) gene is mostly linked to the dissemination of a single IncL/M-type self-transferable plasmid of 62 kb that does not carry any additional resistance gene. OXA-48-type carbapenemases have been identified mainly from North African countries, the Middle East, Turkey and India, those areas constituting the most important reservoirs; however, occurrence of OXA-48 producers in European countries is now well documented, with some reported hospital outbreaks. Since many OXA-48-like producers do not exhibit resistance to broad-spectrum cephalosporins, or only decreased susceptibility to carbapenems, their recognition and detection can be challenging. Adequate screening and detection methods are therefore required to prevent and control their dissemination.